Left Sided Breast Cancer Irradiation ; Prone or Supine Simulation ? - Esra Kekilli; Yasemin Güzle Adaş (Genel Tıp Dergisi)
Aim: The aim of this study was to compare radiation doses of target volumes and critical organs among prone and supine positions for left-sided breast cancer patients who were treated with breast-conserving surgery and adjuvant radiotherapy. Materials and Methods: The doses of critical organs and target volumes were evaluated by using dose-volume histograms on the new radiotherapy plans of twenty patients. Results: The mean heart dose was lower in the prone position (mean heart doses 656cGy and 933cGy respectively p = 0.01). Mean lung doses for prone and supine positions were 396 cGy and 1032 cGy (p =0.01); lung V5 13% and 33% (p =0.01); lung V10 8% and 25% (p =0.01); lung V20 5% and 17% (p =0.01). Conclusion: Considering that lower doses of normal structures may reduce side effects, prone position may be preferred in patients with left breast cancer.